Guerra e pace: una metamorfosi - Magariello, Antonio (Filosofia, 2023)
We try to delineate both the metamorphosis of the clear-cut relationship between peace and war and the semantic shift the latter have undergone. By reconsidering events since the birth of the modern state, through the use of lenses bequeathed by Carl Schmitt, we show how the clear distinction between peace and war has progressively faded to the point of eroding. Starting from the wars of the 1990s up to the most recent ones, the US has progressively deprived both the UN and NATO of their authority, setting itself up as the guardian of global law. No longer having an enemy of equal power to threaten it and expanding ever further east, it has transformed peace into international security and war into an international police operation. Being, in US narrative, a pacified and americanized world, war and peace have disappeared, being now only matters of’US domestic politics’.